(untitled) (Journal of Academic Finance, 2023)
Purpose: The objective of this study is to measure the influence of the ethnicity of the SME manager in the relationship: contingency factors and choice of management control tools in small and medium-sized enterprises. Method: To achieve this objective, a mixed approach is adopted. The qualitative phase relates to 30 interviews and the quantitative phase to a convenience sample of 650 SMEs in Benin. Results: The results highlighted a positive and significant effect between the environment, computerization and decision-making style variables in relation to the choice of management control tools. The results also showed that relations with people of the same ethnicity do not provide any role of moderation in the link between environment, computerization of the SME and the choice of management control tools. Originality : The originality of this study is the introduction of the socio-cultural ethnicity factor in management control.